Exploring Translation and Interpreting Hybrids. The Case of Sight Translation - Dragsted, Barbara; Hansen, Inge (Meta, 2009)
AbstractThis article reports on a comparative study of written translation and sight translation, drawing on experimental data combining keystroke logging, eye-tracking and quality ratings of spoken and written output produced by professional translators and interpreters. Major differences in output rate were observed when comparing oral and written modalities. Evaluation of the translation products showed that the lower output rate in the written condition was not justified by significantly higher quality in the written products. Observations from the combination of data sources point to fundamental behavioural differences between interpreters and translators. Overall, working in the oral modality seems to have a lot to offer in terms of saving time and effort without compromising the output quality, and there seems to be a case for increasing the role of oral translation in translator training, incorporating it as a deliberate practice activity.